Critical Study of Leadership Styles in Handling COVID-19 Crisis - Nangia, Richa; Arora, Richa (Border Crossing, 2021)
The world is passing through an unparalleled crisis, named Covid-19. The world economy is surrounded by it, and therefore on a daily basis, there are many updates in the situation, which is rapidly changing the status of the nation’s worldwide. Some are on the verge of survival, some are trying to get the makeover and some are facing turmoil. In order to overcome this situation, the leaders of the different countries had to plan the strategies to deal with this current situation. Therefore, this paper is focused upon determining the different leadership styles followed by the leaders of the different countries and the effectiveness of these leadership styles in handling the Covid-19 situation. Both primary and secondary data has been collected for the research. This research would encourage the academicians, researchers, management students, corporate managers and employees etc. to understand the impact of different leadership styles followed by the leaders to control any devastating situation that could shatter the economy of any nation. This research would help develop the proper understanding of the different leadership styles and its implementation for determining the effectiveness of the different leadership styles in handling this uncontrollable situation.